Volatilities of trace elements in silicate melts - Norris, C (2016)
The loss rates of volatile elements from silicate melts are of considerable interest to a number of branches of volcanology, petrology, and geochemistry. In the volcanic context emanation coefficients are used as empirical measures of the extent of loss of individual elements in the gas phase. In geochemistry and cosmochemistry relative loss rates control the pattern of element depletions during melting and core segregation on asteroids and proto planets. Incorporation of such differentiated, pre-melted bodies probably influenced the well-known pattern of volatile element depletion in the Silicate Earth. This study makes two independent measurements of the volatilities of the elements Ag, Bi, Cd, Cr, Cu, Ga, Ge, In, Mo, Pb, Sn, Tl, V, W and Zn, in molten silicate. The first includes a series of high pressure (1.5GPa) metal–silicate partitioning experiments used to determine the activities of trace elements in silicate melts. The second involves direct measurement of volatile loss from a representative basaltic melt at oxygen fugacities applicable to planetary formation. Results from this study show that some elements (e.g. indium) are less volatile than previously thought, while others (e.g. copper) are more so. Applying these results to volatile depletion in the Silicate Earth reconciles the supposed overabundance of indium, as suggested by condensation temperatures. Comparing depletion of the Silicate Earth relative to CI meteorites shows a remarkably consistent trend with the measured volatility factors, suggesting that evaporative volatile loss occurred during planetary formation, most likely from planetesimals. The volatile loss data from this study also support the observation of volatile depletion in lunar basalts. Such agreement provides additional evidence that the Moon experienced some degree of volatile loss during its accretion after the giant impact by Theia.